A harm reduction approach to improving peer review by acknowledging its imperfections - Steven J. Cooke; Nathan Young; Kathryn S. Peiman; Dominique G. Roche; Jeff C. Clements; Andrew N. Kadykalo; Jennifer F. Provencher; Rajeev Raghavan; Maria C. DeRosa; Robert J. Lennox; Aminah Robinson Fayek; Melania E. Cristescu; et al. (Canadian Science Publishing, 2024)
This candid perspective written by scholars from diverse disciplinary backgrounds is intended to advance conversations about the realities of peer review and its inherent limitations. Trust in a process or institution is built slowly and can be destroyed quickly. Trust in the peer review process for scholarly outputs (i.e., journal articles) is being eroded by high-profile scandals, exaggerated news stories, exposés, corrections, retractions, and anecdotes about poor practices. Diminished trust in the peer review process has real-world consequences and threatens the uptake of critical scientific advances. The literature on "crises of trust" tells us that rebuilding diminished trust takes time and requires frank admission and discussion of problems, creative thinking that addresses rather than dismisses criticisms, and planning and enacting short- and long-term reforms to address the root causes of problems. This article takes steps in this direction by presenting eight peer review reality checks and summarizing efforts to address their weaknesses using a harm reduction approach, though we recognize that reforms take time and some problems may never be fully rectified. While some forms of harm reduction will require structural and procedural changes, we emphasize the vital role that training editors, reviewers, and authors has in harm reduction. Additionally, consumers of science need training about how the peer review process works and how to critically evaluate research findings. No amount of self-policing, transparency, or reform to peer review will eliminate all bad actors, unscrupulous publishers, perverse incentives that reward cutting corners, intentional deception, or bias. However, the scientific community can act to minimize the harms from these activities, while simultaneously (re)building the peer review process. A peer review system is needed, even if it is imperfect.